OP56 The cost-effectiveness of advance care planning for older adults with end-stage kidney disease. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Sellars, M; Clayton, J; Detering, K; Tong, A; Power, D; Morton, R
Abstract : Background: We aimed to examine hospital costs and outcomes of a nurse-led ACP intervention compared with usual care in the last 12 months of life for older people with end-stage kidney disease (ESKD) managed with haemodialysis. Methods: A case-control study of ACP in adults with ESKD from a major tertiary hospital and a simulation of the natural history of decedents on dialysis, using hospital data, to model the effect of ACP on end-of-life care preferences. Outcomes were assessed in terms of patients' end-of-life treatment preferences being met or not, and costs included all hospital-based care. The cost-effectiveness of ACP was assessed by calculating an incremental cost-effectiveness ratio (ICER), expressed in dollars per additional case of end-of-life preferences being met. Robustness of model results was tested through sensitivity analyses. Results: The mean cost of ACP was AUD$519 per patient. The mean hospital costs of care in last 12 months of life were $100, 579 for those who received ACP versus $87, 282 for those who did not. The proportion of patients in the model who received end-of-life care according to their preferences was higher in the ACP group compared with usual care (68% vs. 24%). The incremental cost per additional case of end-of-life preferences being met was $28, 421. The greatest influence on the cost-effectiveness of ACP was the probability of dying in hospital following dialysis withdrawal, and costs of acute care. Conclusions: Our model suggests nurse-led ACP leads to receipt of patient preferences for end-of-life care, and may represent good value for money.